English about Antivirus Software - Syarif, Hisyam (International Research Journal of Management, IT & Social Sciences, 2015)
Antivirus is a type of software used to detect existing viruses on the computer system. Antivirus software also known as virus protection software. With this software we can find out whether a computer system is exposed to a virus or not. In general, this software runs in the background or the background, and also perform a scan of all files that are accessed. In todays antivirus Progress has been transformed and has many uses associated with the virus. But also the computers performance. The virus code also usually always updated by the antivirus developer. So the computer is ensured its empowering. Even by new viruses though.